Fundamentals of sustainable development - Niko Roorda (London ; New York Routledge, Taylor & Francis Group, 2021)
"Fundamentals of Sustainable Development is an accessible and interdisciplinary textbook that introduces the concept of sustainable development to students from across the disciplines from economics, management, teacher education, arts and humanities to the natural and social sciences. The impact of development needs to be considered beyond the narrow focus of economic, ecological or social concerns. This new edition builds upon the second edition's user-friendly and comprehensive overview of the challenges linked to striving for a sustainable, holistic approach to development. Providing a multifaceted approach to the subject in order to encompass what is referred to as 'people, planet and profit', this third edition provides a complete update of the text, with an emphasis on topics including the Sustainable Development Goals, the circular economy, climate & energy, and sustainable and future-focused entrepreneurship. This stimulating book is an invaluable resource for students and lecturers in all disciplines who have an interest in the sustainability of our planet, and our human society and economy"-- Provided by publisher.
Includes bibliographical references and index
Keywords: Sustainable development--Study and teaching